1995
DOI: 10.1002/ijc.2910610122
|View full text |Cite
|
Sign up to set email alerts
|

The human immunodeficiency virus(HIV) inhibitor 9‐(2‐phosphonylmethoxyethyl)adenine (pmea) is a strong inducer of differentiation of several tumor cell lines

Abstract: 9-(2-phosphonylmethoxyethyl)adenine (PMEA) is the prototype compound of a series of acyclic nucleoside phosphonate derivatives endowed with potent and selective anti-retroviral activity in vitro and in vivo. We have now found that PMEA is also a potent inducer of differentiation of a number of tumor cells, including human erythroleukemia K562 cells, rat choriocarcinoma RCHO cells and human acute promyelocytic leukemic HL-60 cells. At 10 microM PMEA, rat RCHO cell cultures could be almost fully differentiated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…These cells have also been used to screen methodologies or drugs that may inhibit HIV-1 infection or reduce transcriptional activation of the virus [117,[160][161][162][163][164][165][166][167][168][169][170][171][172][173]. These cell lines have also been used in studies of drug toxicity, permeability, and/or effects on cellular activation and differentiation to gain an understanding of what specific drugs might do to cells in the bone marrow [144,154,[174][175][176][177][178][179][180][181][182][183], as well as determining what signaling pathways may play a role or become dysregulated [184][185][186][187][188][189]. Additionally, other studies have been completed that utilize these cells to examine the role that distinct viral determinants as well as specific host factors have on cellular tropism, cellular differentiation, and cytopathology [190][191][192][193].…”
Section: Hl-60mentioning
confidence: 99%
“…These cells have also been used to screen methodologies or drugs that may inhibit HIV-1 infection or reduce transcriptional activation of the virus [117,[160][161][162][163][164][165][166][167][168][169][170][171][172][173]. These cell lines have also been used in studies of drug toxicity, permeability, and/or effects on cellular activation and differentiation to gain an understanding of what specific drugs might do to cells in the bone marrow [144,154,[174][175][176][177][178][179][180][181][182][183], as well as determining what signaling pathways may play a role or become dysregulated [184][185][186][187][188][189]. Additionally, other studies have been completed that utilize these cells to examine the role that distinct viral determinants as well as specific host factors have on cellular tropism, cellular differentiation, and cytopathology [190][191][192][193].…”
Section: Hl-60mentioning
confidence: 99%
“…PMEA has been shown to be a potent differentiation-inducing agent in several tumor cell systems, including human erythroleukemia K562 and myeloid HL-60 cells, as well as the rat choriocarcinoma RCHO cells that we used in the present study to induce choriocarcinoma tumors in rats (Balzarini et al, 1995). In vitro, PMEA induces concentration-dependent differentiation of proliferating choriocarcinoma cytotrophoblast cells into hormonally active giant cells, which no longer proliferate but degenerate and die.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, we have now studied the impact of PMEA on cell cycle distribution and (deoxy)ribonucleotide metabolism in the human erythroleukemia K562, human T‐lymphoid CEM and murine leukemia L1210 tumor cell lines. Because the K562 cell line has been extensively used in our laboratory to investigate the differentiation inducing properties of PMEA [9, 10], the present report is focused on the results obtained with the K562 cells. However, it should be noted that the experiments with CEM and L1210 cells consistently led to similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that PMEA strongly induces differentiation in several in vitro tumor cell models, including human erythroleukemia K562 cells and rat choriocarcinoma RCHO cells [9–11]. Moreover, PMEA effectively inhibits rat choriocarcinoma tumor growth in an in vivo model [12], pointing to the antitumor potential of PMEA and of related acyclic nucleoside phosphonate analogues.…”
Section: Introductionmentioning
confidence: 99%